The height of the tree is 249.5 feet
<h3>How to determine the height of the tree?</h3>
The given parameters are:
- Elevation angle = 80 degrees
- Shadow length (L) = 44 feet
Let the height of the tree be x.
So, we have:
tan(80) = x/44
Multiply both sides by 44
x = 44 * tan(80)
Evaluate
x = 249.5
Hence, the height of the tree is 249.5 feet
Read more about elevation at:
brainly.com/question/19594654
#SPJ1
Check the forward differences of the sequence.
If
, then let
be the sequence of first-order differences of
. That is, for n ≥ 1,
![b_n = a_{n+1} - a_n](https://tex.z-dn.net/?f=b_n%20%3D%20a_%7Bn%2B1%7D%20-%20a_n)
so that
.
Let
be the sequence of differences of
,
![c_n = b_{n+1} - b_n](https://tex.z-dn.net/?f=c_n%20%3D%20b_%7Bn%2B1%7D%20-%20b_n)
and we see that this is a constant sequence,
. In other words,
is an arithmetic sequence with common difference between terms of 2. That is,
![2 = b_{n+1} - b_n \implies b_{n+1} = b_n + 2](https://tex.z-dn.net/?f=2%20%3D%20b_%7Bn%2B1%7D%20-%20b_n%20%5Cimplies%20b_%7Bn%2B1%7D%20%3D%20b_n%20%2B%202)
and we can solve for
in terms of
:
![b_{n+1} = b_n + 2](https://tex.z-dn.net/?f=b_%7Bn%2B1%7D%20%3D%20b_n%20%2B%202)
![b_{n+1} = (b_{n-1}+2) + 2 = b_{n-1} + 2\times2](https://tex.z-dn.net/?f=b_%7Bn%2B1%7D%20%3D%20%28b_%7Bn-1%7D%2B2%29%20%2B%202%20%3D%20b_%7Bn-1%7D%20%2B%202%5Ctimes2)
![b_{n+1} = (b_{n-2}+2) + 2\times2 = b_{n-2} + 3\times2](https://tex.z-dn.net/?f=b_%7Bn%2B1%7D%20%3D%20%28b_%7Bn-2%7D%2B2%29%20%2B%202%5Ctimes2%20%3D%20b_%7Bn-2%7D%20%2B%203%5Ctimes2)
and so on down to
![b_{n+1} = b_1 + 2n \implies b_{n+1} = 2n + 4 \implies b_n = 2(n-1)+4 = 2(n + 1)](https://tex.z-dn.net/?f=b_%7Bn%2B1%7D%20%3D%20b_1%20%2B%202n%20%5Cimplies%20b_%7Bn%2B1%7D%20%3D%202n%20%2B%204%20%5Cimplies%20b_n%20%3D%202%28n-1%29%2B4%20%3D%202%28n%20%2B%201%29)
We solve for
in the same way.
![2(n+1) = a_{n+1} - a_n \implies a_{n+1} = a_n + 2(n + 1)](https://tex.z-dn.net/?f=2%28n%2B1%29%20%3D%20a_%7Bn%2B1%7D%20-%20a_n%20%5Cimplies%20a_%7Bn%2B1%7D%20%3D%20a_n%20%2B%202%28n%20%2B%201%29)
Then
![a_{n+1} = (a_{n-1} + 2n) + 2(n+1) \\ ~~~~~~~= a_{n-1} + 2 ((n+1) + n)](https://tex.z-dn.net/?f=a_%7Bn%2B1%7D%20%3D%20%28a_%7Bn-1%7D%20%2B%202n%29%20%2B%202%28n%2B1%29%20%5C%5C%20~~~~~~~%3D%20a_%7Bn-1%7D%20%2B%202%20%28%28n%2B1%29%20%2B%20n%29)
![a_{n+1} = (a_{n-2} + 2(n-1)) + 2((n+1)+n) \\ ~~~~~~~ = a_{n-2} + 2 ((n+1) + n + (n-1))](https://tex.z-dn.net/?f=a_%7Bn%2B1%7D%20%3D%20%28a_%7Bn-2%7D%20%2B%202%28n-1%29%29%20%2B%202%28%28n%2B1%29%2Bn%29%20%5C%5C%20~~~~~~~%20%3D%20a_%7Bn-2%7D%20%2B%202%20%28%28n%2B1%29%20%2B%20n%20%2B%20%28n-1%29%29)
![a_{n+1} = (a_{n-3} + 2(n-2)) + 2((n+1)+n+(n-1)) \\ ~~~~~~~= a_{n-3} + 2 ((n+1) + n + (n-1) + (n-2))](https://tex.z-dn.net/?f=a_%7Bn%2B1%7D%20%3D%20%28a_%7Bn-3%7D%20%2B%202%28n-2%29%29%20%2B%202%28%28n%2B1%29%2Bn%2B%28n-1%29%29%20%5C%5C%20~~~~~~~%3D%20a_%7Bn-3%7D%20%2B%202%20%28%28n%2B1%29%20%2B%20n%20%2B%20%28n-1%29%20%2B%20%28n-2%29%29)
and so on down to
![a_{n+1} = a_1 + 2 \displaystyle \sum_{k=2}^{n+1} k = 2 + 2 \times \frac{n(n+3)}2](https://tex.z-dn.net/?f=a_%7Bn%2B1%7D%20%3D%20a_1%20%2B%202%20%5Cdisplaystyle%20%5Csum_%7Bk%3D2%7D%5E%7Bn%2B1%7D%20k%20%3D%202%20%2B%202%20%5Ctimes%20%5Cfrac%7Bn%28n%2B3%29%7D2)
![\implies a_{n+1} = n^2 + 3n + 2 \implies \boxed{a_n = n^2 + n}](https://tex.z-dn.net/?f=%5Cimplies%20a_%7Bn%2B1%7D%20%3D%20n%5E2%20%2B%203n%20%2B%202%20%5Cimplies%20%5Cboxed%7Ba_n%20%3D%20n%5E2%20%2B%20n%7D)
Answer:
A, B, F
Step-by-step explanation:
2/3 - x + 1/6 = 6x
Collect like terms
2/3 + 1/6 = 6x + x
(4+1) / 6 = 7x
5/6 = 7x
x = 5/6 ÷ 7
= 5/6 × 1/7
x = 5/42
a) 4 - 6x + 1 = 36x
4 + 1 = 36x + 6x
5 = 42x
x = 5/42
Equivalent to the last step of the simplification above
b) 5/6 - x = 6x
5/6 = 6x + x
5/6 = 7x
This is equivalent to the third step of the simplification
c) 4 - x + 1 = 6x
4 + 1 = 6x + x
5 = 7x
x = 5/7
Not equivalent to any of the steps in the simplification above
d) 5/6 + x = 6x
5/6 = 6x - x
5/6 = 5x
x = 5/6 ÷ 5
= 5/6 × 1/5
x = 5/30
Not equivalent to any of the steps in the simplification above
e) 5 = 30x
x = 5/30
Not equivalent to any of the steps in the simplification above
f) 5 = 42x
x = 5/42
Equivalent to the last step of the simplification above
I also agree with answer C
Answer:
D
Step-by-step explanation:
12-y=2x-5
+5 +5 ( add 5 to both sides)
17-y=2x
-17 -17 (Subtract 17 to get y by itself)
-y=2x-17
divide by -1 because y cant be negative
y=-2x+17
m=-2 and y-intercept= 17
I hope thats right :)